1991
DOI: 10.1007/bf01537613
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in adolescence: Depression, substance use, and other risk factors

Abstract: The interrelationships of depression and suicide with adolescent drug use, delinquency, eating disorders, and the risk factors for these different problems were investigated among 597 9th and 11th graders in an urban high school. There is a strong association of drug use with suicidal ideation among girls, and a stronger relationship with attempts among girls and boys. Suicidal youths are ill-adjusted and display a lack of attachment and commitment to family and school. Causal models indicate that poor interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
161
0
12

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(194 citation statements)
references
References 15 publications
21
161
0
12
Order By: Relevance
“…Maladaptive coping mechanisms include drug use (e.g. alcohol) as a means of temporarily dealing with social and emotional problems (22) that typically characterize adolescence. Such coping strategies may be ineffective and provide only an immediate respite from stressful situations, and may even exacerbate the problems that the adolescent is currently experiencing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Maladaptive coping mechanisms include drug use (e.g. alcohol) as a means of temporarily dealing with social and emotional problems (22) that typically characterize adolescence. Such coping strategies may be ineffective and provide only an immediate respite from stressful situations, and may even exacerbate the problems that the adolescent is currently experiencing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, in one study of youth in Hong Kong, Wong and colleagues (2005) found that suicidal ideation increases for adolescents exposed to suicide attempts, but not necessarily completions. Prior research has also documented the influence deviant friends often have on the negative behaviour of children and youth (Liu, 2004;Kandel, Raveis, & Davies, 1991;Simons & Murphy, 1985). Finally, studies on youth suicide have identified substance use as a significant correlate of suicidal ideation (Kandel, Raveis & Davies, 1991;Metha et al, 1998;Prinstein et al, 2000;Reynolds and Mazza, 1994).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Put another way, suicidal youths are more likely to exhibit weak attachments (DiFilippo & Overholser, 2000;Kandel, Raveis, & Davies, 1991;Perkins & Hartless, 2002). In particular, lack of parental attachment has been empirically shown to impact suicidal ideation (Adams et al, 1994) and completion (Brent et al, 1994).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several large general population studies report suicide attempt rates ranging from 7 to 16% among adolescents [1,15,18,24,28,31]. These studies show clear gender differences, with approximately 4-10% of boys versus 10-20% of girls reporting a history of suicide attempt.…”
Section: Introductionmentioning
confidence: 99%